Stranger danger: family values, childhood, and the American carceral state - Renfro, Paul M. (Oxford University Press, 2020)
"Starting in the late 1970s, a moral panic concerning child kidnapping and exploitation gripped the United States. For many Americans, a series of high-profile cases of missing and murdered children, publicized through an emergent twenty-four-hour news cycle, signaled a 'national epidemic' of child abductions perpetrated by strangers. Some observers insisted that fifty thousand or more children fell victim to stranger kidnappings in any given year. (The actual figure was and remains about one hundred.) Stranger Danger demonstrates how racialized and sexualized fears of stranger abduction -- stoked by the news media, politicians from across the partisan divide, bereaved parents, and the business sector -- helped to underwrite broader transformations in US political culture and political economy. Specifically, the child kidnapping scare further legitimated a bipartisan investment in 'family values' and 'law and order,' thereby enabling the development and expansion of sex offender registries, AMBER Alerts, and other mechanisms designed to safeguard young Americans and their families from 'stranger danger' -- and to punish the strangers who supposedly threatened them"--